Group portrait of campers at Monte Toyon - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Gathering of campers at Monte Toyon is unknown. Considering the religious nature of many documented meetings at Monte Toyon it is quite likely this meeting is religious in nature. In the center of this image, a log cabin structure and flag pole are visible.